Why Are Health Disparities Everyone's Problem? - Cooper, Lisa A. (Book collections on Project MUSE., 2021)
"The author considers an array of factors that produce health inequities, including social conditions, economic policies, the physical environment, institutional factors, health system factors, social relationships, risk behaviors, and biological factors. The author argues that everyone's health is connected, both within their communities and across the globe. Once people realize that, they will see that health inequities are not someone else's problem; rather, they are everyone's problem"--